Electrode composition for electric spray
Patent Information
- Application Number
- JP2023562308
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-09
- Filing Date
- 2022-04-11
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2042-04-11
AI Technical Summary
【0025】 本発明による電気噴射用電極組成物は、電気噴射を通じて超薄膜でありながらも優秀な厚さ均一性を有する電極パターンを具現するのに適合である。また、具現された電極が優秀な電気伝導度を有することができる。ひいては、グリーンシートのようなセラミックシート上に電極を形成するのに適合し得る。また、形成された電極をセラミックグリーンシートと同時焼結する場合に焼結体の形状が完全に維持され得、焼結体の層間分離が防止され得る。また、超薄膜の電極を具現できるため高積層化される積層セラミック部品用内部電極として広く活用され得る。
Smart Images

Figure 0007644842000005 
Figure 0007644842000006 
Figure 0007644842000007
Abstract
Description
[Technical field]
[0001] The present invention relates to electrode compositions, and more particularly to electrode compositions for electrospray. [Background technology]
[0002] Among the electronic components widely used in electronic devices, elements such as capacitors, varistors, suppressors, and MLCCs are co-sintered multilayer ceramic components that are realized by laminating several to several hundred green sheets with electrode patterns printed on them and then sintering the electrodes and green sheets at the same time to realize a single element. Recently, in line with the miniaturization and high performance of electronic devices, much research has been conducted to miniaturize and increase the capacity of these elements.
[0003] In the case of such co-sintered multilayer ceramic parts, in addition to improving the materials of the dielectric and electrodes constituting the green sheets to increase capacity, attempts are being made to increase the number of layers by stacking more green sheets. In order to increase the number of layers in co-sintered multilayer ceramic parts, it is necessary to reduce the thickness of the green sheets corresponding to the dielectric and the electrode patterns, and in order to reduce the size, it is essential to reduce the line width of the electrodes and the gap between the electrodes of the electrode patterns.
[0004] Meanwhile, conventional methods for printing electrode patterns on green sheets have used screen printing and gravure printing, and screen printing and gravure printing have the advantage of being inexpensive. However, these methods can only realize the line width of the electrodes and the spacing between the electrodes at a level of 40 to 80 μm, making it difficult to form smaller and more elaborate fine patterns with these methods. In addition, since the electrode thickness after printing is at a level of 5 to 100 μm, and it is difficult to form an ultra-thin electrode pattern of 1 μm or less, there is a problem that it is difficult to form internal electrodes of highly laminated and miniaturized co-sintered multilayer ceramic parts using conventional screen printing and gravure printing methods. In addition, in order to print ultra-thin electrodes, the viscosity of the electrode composition for printing must be significantly reduced, which leads to problems of uneven printing and reduced printing resolution.
[0005] Recently, there have been attempts to realize fine-patterned electrodes using inkjet printing. Although it is possible to realize an ultra-thin electrode pattern with a thickness of 1 μm or less when forming electrodes using inkjet printing, there are problems such as poor productivity, high cost of ink for manufacturing electrodes, and difficulty in printing electrode patterns on a large area of green sheet.
[0006] Therefore, there is an urgent need to develop a method for easily and inexpensively forming an ultra-thin electrode pattern on a large-area green sheet and an electrode composition suitable for the method. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made in consideration of the above points, and an object of the present invention is to provide an electrode composition for electrospraying suitable for printing an electrode pattern having excellent thickness uniformity while being an ultra-thin film on a ceramic sheet such as a green sheet by electrospraying.
[0008] Another object of the present invention is to provide an electrode composition for electrical spraying that can realize an electrode having excellent electrical conductivity while preventing deformation of the sintered body or interlayer separation due to differences in shrinkage characteristics that occur during simultaneous sintering after being printed on a ceramic sheet such as a green sheet. [Means for solving the problem]
[0009] In order to solve the above problems, the present invention provides an electrode composition for electrospraying to realize an electrode having an average thickness of 1 μm or less when dried, the electrode composition for electrospraying comprising a conductive metal powder having an average particle size of 150 nm or less, a ceramic powder, a binder resin, and a solvent.
[0010] According to an embodiment of the present invention, the electrode composition for electrical spraying may be an electrode composition for realizing an internal electrode of a multilayer ceramic component.
[0011] The conductive metal powder may have an average particle size of 80 nm or less.
[0012] In addition, the number of particles having a particle size of more than twice the average particle size may be 20% or less of the total number of conductive metal powder particles, and the number of particles having a particle size of 0.5 times the average particle size or less may be 20% or less of the total number of conductive metal powder particles.
[0013] In addition, the conductive metal powder may include at least one of a metal selected from the group consisting of Ni, Mn, Cr, Al, Ag, Cu, Pd, W, Mo, and Co, an alloy containing at least one of these metals, and a mixed metal containing at least two of these metals.
[0014] The ceramic powder may have an average particle size that is 0.1 to 0.5 times the average particle size of the conductive metal powder.
[0015] The ceramic powder may contain at least one ceramic powder selected from the group consisting of titania, alumina, silica, cordierite, mullite, spinel, barium titanate, and zirconia.
[0016] In addition, the conductive metal powder may be present in an amount of 10 to 30 wt % based on the total weight.
[0017] The ceramic powder may be included in an amount of 4 to 10 parts by weight based on 100 parts by weight of the conductive metal powder.
[0018] The binder resin may be included in an amount of 2 to 13 parts by weight based on 100 parts by weight of the conductive metal powder.
[0019] The ceramic powder may have an average particle size of 45 nm or less.
[0020] The binder resin may contain 30 to 60 parts by weight of ethyl cellulose per 100 parts by weight of polyvinyl butyral.
[0021] In addition, the viscosity at 25°C may be 50 to 150 cps.
[0022] The present invention also provides an electrospray electrode, which is obtained by electrospraying the electrospray electrode composition of the present invention onto a predetermined region and then drying, and has an average thickness of 1 μm or less.
[0023] Furthermore, according to an embodiment of the present invention, the thickness uniformity may be less than 10%.
[0024] The present invention also provides a multilayer ceramic component including an internal electrode formed by sintering an electrospray electrode according to the present invention. Effect of the Invention
[0025] The electrode composition for electrospray according to the present invention is suitable for forming an electrode pattern having excellent thickness uniformity while being ultra-thin through electrospraying. In addition, the formed electrode can have excellent electrical conductivity. Thus, it is suitable for forming an electrode on a ceramic sheet such as a green sheet. In addition, when the formed electrode is simultaneously sintered with a ceramic green sheet, the shape of the sintered body can be completely maintained and interlayer separation of the sintered body can be prevented. In addition, since it is possible to form an ultra-thin electrode, it can be widely used as an internal electrode for highly laminated multilayer ceramic parts. [Brief description of the drawings]
[0026] [Figure 1] 1 is a SEM photograph of a nickel powder having an average particle size of 75 nm, which is a conductive metal powder included in one embodiment of the present invention. [Diagram 2] FIG. 2 is a SEM photograph of the nickel powder according to FIG. 1 before it is wet classified. [Diagram 3]1 is a SEM photograph of a ceramic powder, which is a barium titanate powder, included in one embodiment of the present invention. [Figure 4] Photographs of electrode compositions for electric spray containing nickel powder according to FIGS. 1 and 2, in which FIG. 4 is a photograph in which the nickel powder is uniformly dispersed with the ceramic powder without settling, and FIG. 5 is a photograph in which phase separation occurs between the nickel powder and the ceramic powder as the nickel powder settles. [Diagram 5] Photographs of electrode compositions for electric spray containing nickel powder according to FIGS. 1 and 2, in which FIG. 4 is a photograph in which the nickel powder is uniformly dispersed with the ceramic powder without settling, and FIG. 5 is a photograph in which phase separation occurs between the nickel powder and the ceramic powder as the nickel powder settles. [Figure 6] These are optical microscope photographs of electrodes that have been dried after electrospraying an electrode composition for electrospraying. FIG. 6 is a photograph of an electrode pattern with excellent continuous electrode surface formability, with no areas in the electrode pattern where the electrode is not formed, and FIG. 7 is a photograph of an electrode pattern with areas in the electrode pattern where the electrode is not formed (areas indicated by circles), and where a continuous electrode surface has not been partially formed. [Figure 7] These are optical microscope photographs of electrodes that have been dried after electrospraying an electrode composition for electrospraying. FIG. 6 is a photograph of an electrode pattern with excellent continuous electrode surface formability, with no areas in the electrode pattern where the electrode is not formed, and FIG. 7 is a photograph of an electrode pattern with areas in the electrode pattern where the electrode is not formed (areas indicated by circles), and where a continuous electrode surface has not been partially formed. [Figure 8] FIG. 8 is a photograph of an electrode pattern having excellent continuous electrode surface formability with no areas where electrodes are not formed in the electrode pattern, and FIG. 9 is a photograph of an electrode pattern having partially fallen electrodes where electrodes are not formed in the electrode pattern and thus partially failing to form a continuous electrode surface. [Figure 9]FIG. 8 is a photograph of an electrode pattern having excellent continuous electrode surface formability with no areas where electrodes are not formed in the electrode pattern, and FIG. 9 is a photograph of an electrode pattern having partially fallen electrodes where electrodes are not formed in the electrode pattern and thus partially failing to form a continuous electrode surface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention may be embodied in many different forms and is not limited to the embodiments set forth herein.
[0028] The electrode composition according to one embodiment of the present invention is suitable for an electric spray method and can realize an ultra-thin electrode having an average thickness of 1.0 μm or less, preferably 0.6 μm or less when dried, and is realized by including a conductive metal powder having an average particle size of 150 nm or less, a ceramic powder, a binder resin, and a solvent. In addition, since the composition is suitable for forming an electrode on a green sheet and can realize an ultra-thin electrode, it is particularly suitable for realizing an internal electrode of a multilayer ceramic part such as an MLCC that requires high lamination.
[0029] The conductive metal powder provides conductivity and forms the body of the electrode after sintering, and any conductive metal powder commonly used to manufacture electrodes for electronic components may be used without limitation. For example, the conductive metal powder may include at least one metal selected from the group consisting of nickel, manganese, chromium, aluminum, silver, copper, palladium, tungsten, molybdenum, and cobalt, an alloy containing at least one of the metals, and a mixed metal containing at least two of the metals. However, when sintering simultaneously with the ceramic green sheet, the conductive metal powder may include at least one metal selected from the group consisting of palladium, silver-palladium alloy, silver, nickel, and copper in consideration of the sintering temperature, and more preferably includes nickel in consideration of heat resistance, conductivity, and material cost.
[0030] In addition, the conductive metal powder may have an average particle size of 150 nm or less, preferably 100 nm or less, more preferably 80 nm or less. If the average particle size of the conductive metal powder exceeds 150 nm, the thickness of the electrode dried after electrospraying may exceed 1 μm, or the formed dried electrode may not form a continuous electrode surface, or even if a dried electrode having a thickness of 1 μm is formed, the thickness uniformity may be very uneven, making it difficult to realize a high-laminar laminated ceramic part of a good quality. Meanwhile, the conductive metal powder may have an average particle size of 5 nm or more, more preferably 10 nm or more, more preferably 20 nm or more. If the average particle size is less than 5 nm, it is difficult to realize the conductive metal powder itself, and material costs may increase. In addition, the metal powder is required to be finely divided to ensure dispersibility, but degreasing may be difficult due to organic compounds such as dispersants added to ensure dispersibility, and therefore separation between green sheet layers may occur when the laminated ceramic part is sintered. In addition, if a separate dispersant is not included, when the average particle size of the conductive metal powder is too small, the dispersibility decreases and the conductive metal powder aggregates to form coarse secondary particles, which is undesirable because it may be difficult for the resulting dry electrode to form a continuous electrode surface or thickness unevenness may become severe.
[0031] In addition, the conductive metal powder may have a particle size distribution in which the number of particles having a particle size of two or more times the average particle size is 20% or less, more preferably 15% or less, more preferably 10% or less, and even more preferably 5% or less, and the number of particles having a particle size of 0.5 times or less the average particle size is 20% or less, more preferably 10% or less, of the total number of conductive metal powders. This is suitable for minimizing the formation of secondary particles due to aggregation of conductive metal powder in an electrode composition supplied for electrical spraying, and minimizing or preventing sedimentation of conductive metal powder in a spray solution chamber in an electrical spraying device. This is advantageous for forming a continuous electrode surface in which there is no region where the electrode composition is not sprayed, where there is no electrode partially present in a dry electrode, and may be advantageous for preventing deterioration of electrode appearance quality, such as uneven electrical properties such as resistance at different positions of an electrode formed by electrical spraying and uneven thickness of an implemented electrode.
[0032] In addition, the conductive metal powder may be included in an amount of 30 wt % or less, more preferably 10 to 30 wt %, and more preferably 20 to 30 wt %, based on the total weight of the electrode composition. If the conductive metal powder is included in an amount exceeding 30 wt %, sedimentation or precipitation of the conductive metal powder may occur in the electrode composition supplied for electrospraying, which may result in non-uniform spraying of the conductive powder during electrospraying. In addition, it may be difficult to control the thickness of the electrode realized by electrospraying. In addition, if the conductive metal powder is included in an amount less than 10 wt %, the electrically sprayed dried electrode or sintered electrode may form islands like water droplets, which may reduce the continuity of the electrode surface or cause the dried electrode to have an uneven thickness, making it difficult to realize the desired electrode.
[0033] Meanwhile, the electrode composition has high electrical conductivity due to the conductive metal powder, but the high electrical conductivity can make electrical spraying difficult. For this reason, the electrode composition includes ceramic powder, which allows the electrode composition to be adjusted to an electrical conductivity suitable for electrical spraying. In addition, the electrode composition is processed on the green sheet, which can prevent deformation such as crushing of the sintered body due to the sintering temperature difference between the electrode and the green sheet that occurs during simultaneous sintering and the resulting difference in shrinkage characteristics. Furthermore, after sintering, the ceramic components derived from the ceramic powder can move to the surface side of the sintered electrode and be layer-separated from the conductive components derived from the sintered conductive metal powder, thereby increasing the dielectric constant, which can contribute to improving the characteristics of multilayer ceramic parts such as MLCCs.
[0034] The ceramic powder may have an average particle size of 100 nm or less, or 70 nm or less, 45 nm or less, or 1 to 30 nm. The ceramic powder may have an appropriate average particle size in consideration of the average particle size of the conductive metal powder, and more specifically, may have an average particle size smaller than the average particle size of the conductive metal powder, 0.5 times or less, more preferably 0.3 times or less, which is advantageous in preventing the electrode from shrinking faster than the green sheet during sintering. When a conductive metal powder having an average particle size of 80 nm is used, the average particle size of the ceramic powder may be 20 nm or less. However, if the average particle size of the ceramic powder is smaller than the average particle size of the conductive metal powder, 0.1 times or less, the amount of resin added may need to be increased due to an increase in the surface area of the particles, which may cause uneven thickness of the dried and / or sintered electrode, and the shrinkage rate of the electrode may increase during sintering, which may be undesirable.
[0035] Meanwhile, the ceramic powder may also be advantageous in maintaining a uniform dispersed phase if the ratio of coarse particles having a particle size more than twice the average particle size is low. Accordingly, the number of particles having a particle size more than twice the average particle size may be 20% or less, more preferably 10% or less, and even more preferably 5% or less of the total number of ceramic powder particles.
[0036] In addition, the ceramic powder may be any known ceramic powder without limitation, and may include, for example, at least one ceramic powder selected from the group consisting of titania, alumina, silica, cordierite, mullite, spinel, barium titanate, and zirconia. In this case, when the ceramic powder is used for forming an internal electrode by electrospraying an electrode composition onto a green sheet, it may be selected to have a common component with the dielectric component of the green sheet, which may facilitate control of the shrinkage characteristics between the green sheet and the electrode during co-sintering, and may be advantageous in improving the bonding and adhesion characteristics between the electrode and the green sheet. Meanwhile, when the ceramic powder is barium titanate, it may be selected to have a composition in which Ca and Zr are partially dissolved (Ba 1-x Ca x )TiO3, Ba(Ti 1-y Ca y )O3, (Ba 1-x Ca x )(Ti 1-y Zr y )O3 or Ba(Ti 1-y Zr y )O3 also belongs to the category of barium titanate.
[0037] The ceramic powder may be included in an amount of 4 to 10 parts by weight, more preferably 4 to 7 parts by weight, based on 100 parts by weight of the conductive metal powder. If the ceramic powder is included in an amount less than 4 parts by weight, it may be difficult to control the thickness of the electrode to be realized. In addition, it is difficult to control the shrinkage characteristics when sintered simultaneously with the ceramic green sheet, and cracks and peeling of the electrode after sintering may occur frequently. In addition, if the ceramic powder is included in an amount exceeding 10 parts by weight, the electrical conductivity of the electrode to be realized may decrease, and the degree of shrinkage of the electrode during sintering may be excessive.
[0038] Meanwhile, the particle size of the conductive metal powder and ceramic powder in the present invention is a value based on particle size measurement by dynamic light scattering, and is a volumetric particle size, and the average particle size means a particle size corresponding to D50 in cumulative volumetric particle size distribution. In addition, the measuring device may be a known measuring device capable of counting nano-sized powder particle size, and may be measured by a measuring device such as Zetasizer series, APS-100, etc.
[0039] In addition, the conductive metal powder having an average particle size of 150 nm or less can be realized by using a dry plasma powder synthesis method such as PVD or CVD, which can be advantageous in producing a powder with a clean particle surface. In addition, it can be advantageous to obtain a conductive metal powder having a desired particle size and distribution by performing a wet classification process using a known gravity drop method or centrifugation on the conductive metal powder obtained by using the dry plasma powder synthesis method. In this case, it is preferable to use forced classification by centrifugation, and it is preferable to use a continuous centrifuge for production efficiency. The continuous centrifuge can adjust the average particle size by adjusting the rotation speed and the input amount per minute of the centrifuge, and can control the number ratio of coarse particles that induce rapid sedimentation of the conductive metal powder in the electrode composition and inhibit uniform dispersion, for example, conductive metal powder having a particle size of more than twice the average particle size, so as to be low. If the rotation speed of the centrifuge is too high, the production yield rate is significantly reduced, and if it is too low, the removal rate of coarse particles that inhibit uniform dispersion is reduced. In addition, if the amount of input is too large, the time of receiving the centrifugal force in the centrifuge chamber is short, so it is difficult to remove large particles, and if the amount of input is too small, the efficiency is improved but the production time is long, which is undesirable. In addition, a filtration process can be further performed to finely control the particle size distribution of the conductive metal powder to a desired level, and the filtration process can be performed through a conventional process of removing coarse particles using a known filter medium, so the present invention is not particularly limited thereto. Specifically, FIG. 1 is an SEM photo of the conductive metal powder used in Example 4, and it can be seen that the conductive metal powder shown in FIG. 2 has a low coarse particle ratio through wet classification using a centrifuge method, so that the electrode composition has a good dispersion state as shown in FIG. 4. On the other hand, when the conductive metal powder has a large amount of coarse particles, it can be confirmed that the conductive metal powder sediments a lot and is phase-separated from the ceramic powder as shown in FIG. 5.
[0040] In addition, the ceramic powder may be manufactured by appropriately utilizing known powder technology and fine particle control technology using a commercially available ceramic powder so as to have a desired particle size distribution, and as a specific means, it may be manufactured by adjusting factors such as various known pulverization and classification methods, related equipment, and pulverization conditions and pulverization time using the same. As an example, in the case of a pulverizer, any one of a mechanical pulverizer using a blade mill or a super rotor, or an airflow pulverizer that uses a high-speed airflow of high-pressure air to cause particles to collide with each other against a wall and pulverize them can be used, or the pulverized material pulverized using any one of the above can be fed again into another pulverizer and pulverized to adjust the pulverization level. In addition, the ceramic powder may be classified to have a desired particle size distribution through a centrifugal method using a classifier that classifies pulverized material, such as a centrifugal air force disperser, a disperser that uses a physical dispersing force such as a high-speed airflow to prevent the aggregation of fine particles, or a wet classification method, and a detailed description thereof will be omitted in the present invention.
[0041] In addition, the electrode composition includes a binder resin together with the conductive metal powder and ceramic powder, and thereby, the electrode forming property through electrospray and the adhesive property with the electrosprayed surface can be exhibited. The binder resin can be any binder resin used in a conventional electrode composition, and examples thereof include polyvinyl butyral, polyvinyl butyral aldehyde, polyvinyl alcohol, acrylic resin, epoxy resin, phenol resin, alkyd resin, cellulose polymer, rosin resin, etc. However, in consideration of the electrode printability through electrospray and the adhesive force and adhesion force with the electrosprayed surface, especially the green sheet surface, the binder resin can be a mixture of polyvinyl butyral and ethyl cellulose. In this case, the binder resin can include 30 to 60 parts by weight of ethyl cellulose for 100 parts by weight of polyvinyl butyral, and thereby, improved printability and surface adhesion properties can be exhibited. If the amount of ethyl cellulose is more than 60 parts by weight, the size of the slurry particles sprayed from the spray nozzle during electrical spraying may not be refined, and the electrode film dried after electrical spraying may become too hard and the adhesion to the electrically sprayed surface may decrease, which may cause the electrode to peel off from the sprayed surface during sintering. Also, if the amount of ethyl cellulose is less than 30 parts by weight, the electrode printability through electrical spraying may decrease.
[0042] In addition, it is preferable to use polyvinyl butyral and ethyl cellulose having a weight average molecular weight of 100,000 or less, for example, 10,000 to 100,000, which can easily realize a viscosity suitable for electric spraying. If a weight average molecular weight of more than 100,000 is used, electric spraying may become difficult due to an excessive increase in viscosity.
[0043] The binder resin may be included in an amount of 13 parts by weight or less, more preferably 10 parts by weight or less, and even more preferably 2 to 10 parts by weight, based on 100 parts by weight of the conductive metal powder. If the binder resin exceeds 13 parts by weight, cracks may occur in the electrode during sintering, or separation may occur between the laminated green sheet layers when sintered together with the green sheet. If the binder resin is less than 2 parts by weight, sedimentation of the metal powder or ceramic powder in the electrode composition may occur, or dispersibility may be hindered, and the electrode may peel off from the sprayed surface before drying and sintering after spraying.
[0044] In addition, the electrode composition includes a solvent, which can be used in a spraying solution during electrical spraying, does not affect the surface to be electrically sprayed, such as the green sheet and the conductive metal powder and ceramic powder described above, and can dissolve the binder resin. In the case of a solvent used in a known electrode composition, the solvent can be selected without any restrictions. For example, one or more organic solvents such as dihydroterpineol, dihydroterpineol acetate, terpineol, octanol, n-paraffin, decanol, tritetracanol, dibutyl phthalate, butyl acetate, butyl carbitol, butyl carbitol acetate, isobornyl acetate, isobornyl propionate, isobornyl butyrate, isobornyl isobutyrate, ethylene glycol monobutyl ether acetate, dipropylene glycol methyl ether acetate, ethyl acetate, butyl acetate, and hexyl acetate may be used. Preferably, a mixed solvent of dihydroterpineol and dihydroterpineol acetate or a mixed solvent of dihydroterpineol acetate and ethyl acetate may be used. Preferably, a mixed solvent of dihydroterpineol and dihydroterpineol acetate may be used.
[0045] Meanwhile, the electrode composition for electrospray according to an embodiment of the present invention may be embodied as a photosensitive electrode composition, in which the binder resin includes a photosensitive resin, and the photosensitive electrode composition may further include a monomer and a photoinitiator.
[0046] The binder resin includes a photosensitive resin, which serves as a binder for the photosensitive electrode composition and maintains the binding strength of the dried electrode and provides solubility in a developer. The photosensitive resin can be cured by intermolecular crosslinking under the action of active energy such as ultraviolet light or electron beams to form a cured coating film, or the intermolecular crosslinking can be broken to dissolve in a developer.
[0047] The photosensitive resin may be any photosensitive resin commonly used in the field of photosensitive electrode pastes without limitation. It may also be a positive-type or negative-type photosensitive resin. For example, the photosensitive resin may be a photosensitive binder resin used in a photosensitive resin composition, such as an acrylate-based, cellulose-based, novolac acrylic-based, water-soluble polymer, polyimide, or a precursor thereof. However, the photosensitive resin may preferably be a negative-type acrylate-based photosensitive binder. As the acrylate-based photosensitive binder, various conventionally known photosensitive resins (photosensitive prepolymers) may be used, such as resins having ethylenically unsaturated bonds such as vinyl groups, allyl groups, acryloyl groups, and methacryloyl groups, or photosensitive functional groups such as propargyl groups, for example, acrylic copolymers having ethylenically unsaturated groups in their side chains, unsaturated carboxylic acid-modified epoxy resins, or resins to which polybasic acid anhydrides have been added. Specifically, the photosensitive resin may include an acrylate-based copolymer in which at least two monomers selected from glycidyl methacrylate (GMA), methyl methacrylate (MMA), isobornyl methacrylate (IBOMA), benzyl methacrylate, methacrylic acid (MMA), acrylic acid (AA), and a styrene monomer are copolymerized. As a more specific example, the photosensitive resin may be a glycidyl methacrylate-methyl methacrylic acid copolymer, a glycidyl methacrylate-methyl methacrylate-methyl methacrylate-isobornyl methacrylate copolymer, or a methyl methacrylate-benzyl methacrylate-methacrylic acid copolymer.
[0048] In addition, the photosensitive resin according to an embodiment of the present invention may be an acrylate-based copolymer in which methacrylic acid, methyl methacrylate, and isobornyl methacrylate are copolymerized, and the methacrylic acid is contained in an amount of 15.5 to 19.5 mol % and the weight average molecular weight is 8,000 to 15,000. More preferably, the photosensitive resin may be a copolymer containing 25 to 40 mol % of methyl methacrylate and the remaining amount of isobornyl methacrylate. Through this, it is advantageous to realize an electrode pattern having excellent quality, resolution, and photosensitivity and preventing residue.
[0049] In addition, the acrylate copolymer may be introduced by reacting a compound having an epoxy or isocyanate functional group with a carboxy functional group in the acrylate copolymer to adjust the acid value. In this case, the compound having an epoxy group may be, for example, one that includes at least one functional group selected from a methylene functional group, a vinyl functional group, and an allyl functional group at its terminal, and more specifically, may be allyl glycidyl ether. In addition, the compound having an isocyanate functional group may be, for example, 2-acryloyloxyethyl isocyanate.
[0050] In addition, the acrylate copolymer with the adjusted acid value may have an acid value of 25 to 100 mgKOH / g, thereby exhibiting excellent photosensitivity and developability.
[0051] The glass transition temperature of the photosensitive resin, which is an acrylate copolymer, may be 20 to 150°C.
[0052] According to an embodiment of the present invention, the photosensitive resin may include polyimide or a precursor thereof in addition to the acrylate-based photosensitive resin. At this time, the content of polyimide or a precursor thereof may be 10 to 60 parts by weight based on 100 parts by weight of the acrylate-based resin, which may be more advantageous in achieving the object of the present invention.
[0053] Meanwhile, the binder resin containing the photosensitive resin may further include a polyvinyl butyral resin. A binder resin consisting of only a photosensitive resin may have poor adhesion to a surface to be electrosprayed, for example, a green sheet. Thus, the binder resin may further include a polyvinyl butyral resin, thereby achieving improved adhesion and adhesion to the green sheet. The polyvinyl butyral resin may be included in the binder resin in an amount of 10 to 50 wt %, and if it is included in an amount exceeding 50 wt %, defects such as residues may increase during development after exposure, and if it is included in an amount less than 10 wt %, the effect of improving adhesion may be small. At this time, the polyvinyl butyral resin is preferably one having a weight average molecular weight of 100,000 or less, for example, 10,000 to 100,000, in consideration of the fact that the electrode composition to be embodied must maintain a low viscosity.
[0054] In addition, the monomer contains a carbon-carbon double bond, and the double bond is converted into a single bond by radicals excited by active energy such as ultraviolet light or electron beams, and a polymerization reaction is performed to form a hardened structure in the photosensitive electrode composition. The monomer is not particularly limited as long as it is a monomer commonly used in the field of photosensitive pastes. For example, the monomer may be a multifunctional monomer such as a difunctional, trifunctional, or tetrafunctional monomer. More specifically, the multifunctional monomer may be an acrylic ester selected from trimethylolpropane triacrylate, trimethylolpropane ethoxylated triacrylate, pentaerythritol tri-acrylate, or pentaerythritol tetra-acrylate, but is not limited thereto.
[0055] In addition, the monomer may be included in an amount of 10 to 100 parts by weight based on 100 parts by weight of the photosensitive resin. If the content of the monomer is less than 10 parts by weight, the hardening density of the exposed pattern may be weak, and if it exceeds 100 parts by weight, the pattern characteristics may be deteriorated, and there may be a risk of an increase in resistance due to organic residue after hardening, or separation between stacked green sheet layers.
[0056] According to an embodiment of the present invention, an oligomer may be further included as a component that forms a cured structure by radicals, similar to the above-mentioned monomer. The oligomer may be any oligomer commonly used in photosensitive electrode compositions without limitation, and may be, for example, an acrylate having a molecular weight of 1000 or less. The oligomer may be included in an amount of 10 to 100 parts by weight based on 100 parts by weight of the above-mentioned photosensitive resin, but is not limited thereto.
[0057] In addition, the photoinitiator is a compound that generates radicals and causes a chemical reaction when exposed to active energy such as ultraviolet light or an electron beam, and is not particularly limited as long as it is a photopolymerization initiator commonly used in the field of photosensitive electrode compositions. For example, acetophenone-based compounds, benzophenone-based compounds, thioxanthone-based compounds, benzoin-based compounds, triazine-based compounds including monophenyl, oxime-based compounds, carbazole-based compounds, diketone compounds, sulfonium borate-based compounds, diazo-based compounds, non-imidazole-based compounds, etc. may be used as the photoinitiator. Specifically, the photoinitiator is benzophenone, methyl o-benzoylbenzoate, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, 4,4'-dichlorobenzophenone, 4-benzoyl-4'-methyldiphenyl ketone, dibenzyl ketone, fluorenone, 2,2'-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2-hydroxy-2-methylpropiophenone, pt-butyldichloroacetophenone, thioxanthone, 2-methylthioxanthone, 2-chlorothioxanthone, 2-isopropylthioxanthone. , diethylthioxanthone, 4-azidobenzalacetophenone, 2,6-bis(p-azidobenzylidene)cyclohexanone, 6-bis(p-azidobenzylidene)-4-methylcyclohexanone, 1-phenyl-1,2-butanedione-2-(o-methoxycarbonyl)oxime, 1-phenyl-propanedione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-propanedione-2-(o-benzoyl)oxime, 1,3-diphenyl-propanetrione-2-(o-ethoxycarbonyl)oxime, 1-phenyl-3-ethoxy-propanetrione-2-(o-benzoyl)oxime, At least one selected from the group consisting of 1,2-octanedione, 1-[4-(phenylthio)-2-(O-benzoyloxime)], 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, Michler's ketone, 2-methyl-[4-(methylthio)phenyl]-2-morpholino-1-propanone, naphthalenesulfonyl chloride, quinoline sulfonyl chloride, N-phenylthioacridone, 4,4'-azobisisobutyronitrile, diphenyl disulfide, benzothiazole disulfide, triphenylphosphine, benzoin peroxide, and photoreducible dyes such as eosin and methylene blue, ascorbic acid, and triethanolamine may be used.
[0058] The photoinitiator may be contained in an amount of 1 to 50 parts by weight based on 100 parts by weight of the binder resin. If the content of the photoinitiator is less than 1 part by weight, the hardening density of the exposed area may decrease, and the hardened coating may be affected during the development process. If the content of the photoinitiator is more than 50 parts by weight, the upper part of the dried coating may absorb too much light, making it difficult to form the desired pattern.
[0059] Meanwhile, an azide-based photocrosslinking agent compound may be used together with or instead of a photoinitiator, more specifically, a compound in which an azide group, which is a photocrosslinkable functional group, is substituted at both ends of a linear alkylene group having 4 to 20 carbon atoms, and such a compound is advantageous in that the amount of photoinitiator can be reduced since crosslinking can be performed without a photoinitiator. Specific examples of such a compound include 1,4-diazidobutane, 1,5-diazidopentane, 1,6-diazidohexane, 1,7-diazidoheptane, 1,8-diazidooctane, 1,10-diazidodecane, 1,12-diazidododecane, or a mixture thereof.
[0060] In addition, the total weight of the binder resin including the photosensitive resin and the monomer may be 13 parts by weight or less, more preferably 10 parts by weight or less, and even more preferably 2 to 10 parts by weight, per 100 parts by weight of the conductive metal powder. If the binder resin exceeds 13 parts by weight, cracks may occur in the electrode during sintering, or separation may occur between the laminated green sheet layers when sintered together with the green sheet. If the binder resin is less than 2 parts by weight, sedimentation of the metal powder or ceramic powder in the electrode composition may occur or dispersibility may be hindered, and the electrode may peel off from the sprayed surface before drying and sintering after spraying.
[0061] Meanwhile, it is clear that the specific types and contents of the binder resin including the photosensitive resin, the monomer and the photoinitiator can be determined by comprehensively considering the manufacturing method through electric spraying, the use of the internal electrodes of the multilayer ceramic component, the thickness, line width, and spacing of the internal electrodes to be realized, and the materials and particle sizes of the metal powder and the ceramic powder.
[0062] In addition, the electrode composition or photosensitive electrode composition may further include additives such as a dispersant, a plasticizer, a leveling agent, a thixotropic agent, a slip agent, and a hardening accelerator in addition to the above-mentioned components. The additives may be used without limitation in the case of additives contained in known electrode compositions, and therefore the present invention is not specifically limited thereto.
[0063] For example, the dispersant is included to provide dispersion stability of the metal powder and the ceramic powder, and is not particularly limited as long as it is a dispersant commonly used in electrode compositions. The dispersant may be at least one selected from the group consisting of oleic acid, polyethylene glycol fatty acid ester, glycerin ester, sorbitan ester, propylene glycol ester, sugar ester, fatty acid alkanolamide, polyoxyethylene fatty acid amide, polyoxyethylene alkylamine, amine oxide, and poly-12-hydroxystearic acid.
[0064] Meanwhile, the additives including the dispersant may be included in an amount of 10 to 50 parts by weight based on 100 parts by weight of the binder resin. If the additives are included in an amount less than 10 parts by weight, it may be difficult to achieve the intended effect through the additives. Also, if the additives exceed 50 parts by weight, physical properties such as the conductivity of the electrode composition and the thickness uniformity of the dried electrode and / or sintered electrode realized after spraying may be deteriorated.
[0065] In addition, the electrode composition containing the above-mentioned components may have a viscosity of 50 to 150 cps, more preferably 70 to 100 cps, which is suitable for electrical spraying and is advantageous for realizing an ultra-thin dry electrode after electrical spraying. If the viscosity is less than 50 cps, the dispersed conductive metal powder and ceramic powder may quickly precipitate, which may deteriorate the dispersibility. If the viscosity exceeds 150 cps, it may be difficult to precisely control the thickness through electrical spraying, which may make it difficult to manufacture an electrode with a thin thickness. Meanwhile, the viscosity here is a result measured by a Brookfield rotational viscometer LV according to ISO 554 under the conditions of a temperature of 25°C, a relative humidity of 65%, and 10 rpm.
[0066] Meanwhile, the electrode composition may be realized by mixing a conductive metal powder, a ceramic powder, a binder resin, and a solvent, and then dispersing the conductive metal powder and the ceramic powder. At this time, since a lot of heat is generated by the fine powder during mixing and dispersion, it may be more advantageous to mix and disperse using a high-pressure dispersing device or a bead mill. In addition, it is preferable that the electrode composition is maintained in a maximum dispersed state until it is transferred to the inside of the electric spraying device and sprayed through a nozzle, and for this purpose, a stirring device capable of continuously maintaining the dispersed state may be further included in the spraying solution tank in the electric spraying device, and the stirring device may be a known stirring device such as an impeller, and the present invention is not particularly limited thereto.
[0067] The electrode composition may be sprayed onto a target surface, such as a ceramic green sheet, using a conventional electric spraying device to form a desired electrode pattern, and then dried and sintered to form an electrode. In this case, the electrode may have an average thickness of 1 μm or less when dried, and an average thickness of 0.3 to 1.0 μm or less after sintering, for example.
[0068] In addition, the electrode surface of the electrode that is applied to the pattern and dried can have a continuous electrode surface without any uncoated areas. In addition, since it is possible to form a large area, for example, on a ceramic green sheet having an area of 20 cm x 20 cm or more, the area of the continuous electrode surface that is dried through electric spraying can be formed to be 70% or more, preferably 80% or more, and more preferably 90% or more of the area of the ceramic green sheet.
[0069] In addition, preferably, the continuous electrode surface on which the thickness of the dried electrode has been measured is divided into five different non-overlapping regions, and the thickness uniformity according to the following formula 1 using the average value of the five average thicknesses measured for each region and the standard deviation thereof may be within 10%, more preferably within 5%, and more preferably within 3%. Here, the thickness uniformity (%) means that the less the deviation from the average thickness of each region, i.e., the closer the standard deviation is to 0, the better the thickness uniformity. [Formula 1] Thickness uniformity (%) = [(Standard deviation (nm) for the average thickness of five regions) / (Average value (nm) for the average thickness of five regions)] x 100 Meanwhile, the average thickness of the dry electrode and the average thickness of the sintered electrode defined in the present invention may be measured by a thickness measurement method known as Alpha Step, and a known measuring device for measuring thickness by this method may be used without any limitation for the thickness measurement.
[0070] Meanwhile, after electrospraying the photosensitive electrode composition for electrospraying, a desired electrode pattern can be realized under known exposure and development conditions before sintering. For example, the exposure and development conditions after electrospraying may be a drying temperature of 50 to 70°C and a UV exposure dose of 100 mJ to 700 mJ after electrospraying. For example, a Na2CO3 solution may be used as the developer, and the concentration of the developer may be 0.1 to 4 wt %. The development time may be 20 to 100 seconds. [Mode for carrying out the invention] The present invention will be described in more detail through the following examples. However, the following examples should not be construed as limiting the scope of the present invention, but rather as being intended to aid in the understanding of the present invention. <Example 1> Nickel powder with an average particle size of 438 nm was produced through dry plasma. The nickel powder was then subjected to wet classification using a centrifuge method to prepare a conductive metal powder with an average particle size of 147.1 nm, with particles having a particle size of more than twice the average particle size making up 15% of the total nickel powder, and particles having a particle size of less than 0.5 times the average particle size making up 18% of the total nickel powder.
[0071] In addition, a ceramic powder having an average particle size of 155 nm and BaTiO3 was prepared as the ceramic powder, and then it was wet classified using a centrifuge method to prepare a ceramic powder having an average particle size of 65.8 nm and a particle size distribution in which particles having a particle size of 2 times or more of the average particle size accounted for 10% of the total ceramic powder, and particles having a particle size of 0.5 times or less of the average particle size accounted for 9% of the total ceramic powder.
[0072] Then, the conductive metal powder, which is nickel having the particle size controlled as described above, the ceramic powder, and the binder resin, which is a mixture of 100 parts by weight of polyvinyl butyral having a weight average molecular weight of about 70,000 and 45 parts by weight of ethyl cellulose having a weight average molecular weight of 40,000, were mixed in a mixed solvent in which dihydroterpineol acetate and ethyl acetate were mixed in a weight ratio of 1:1 as a solvent. Specifically, 6.8 parts by weight of the ceramic powder and 8 parts by weight of the binder resin were mixed with 100 parts by weight of the conductive metal powder, and the weight of the conductive metal powder was mixed to be 25% by weight of the total composition, to prepare an electrode composition for electric spraying as shown in Table 1 below, which has a viscosity of 80 cps at a temperature of 25°C.
[0073] The viscosity of the prepared electrospray electrode composition was measured using a Brookfield rotational viscometer LV according to ISO 554 under conditions of a temperature of 25° C., a relative humidity of 65%, and a speed of 10 rpm. <Examples 2 to 14> Electrode compositions for electrical spraying were prepared by carrying out the same procedure as in Example 1, but the content, average particle size, particle size distribution of the conductive metal powder, the content, average particle size of the ceramic powder, and / or the viscosity of the electrode composition were changed as shown in Table 1 or Table 2 below.
[0074] The ceramic powder used here had its particle size adjusted through wet classification so that particles with a particle size of more than twice the average particle size were within 10% of the total ceramic powder, and particles with a particle size of less than 0.5 times the average particle size were within 10% of the total ceramic powder. <Comparative Example 1> The electrode composition for electric spray was prepared in the same manner as in Example 1, but the average particle size of the conductive metal powder was changed as shown in Table 1 below. <Experimental Example 1> A ceramic green sheet having a thickness of 5 μm was prepared from a ceramic slurry having a viscosity of 300 cps, which was prepared by mixing 100 parts by weight of a ceramic component, which was barium titanate, with 10 parts by weight of a polyvinyl butyral binder resin and butyl carbitol acetate as a solvent. The electrode compositions for electrospray according to the examples and comparative examples were electrosprayed on the ceramic green sheet at a discharge speed (3 ml / min per hole) using an electrospray device under conditions of 18°C, relative humidity of 30%, an air gap between the nozzle and the ceramic green sheet surface of 24 cm, and an applied voltage of 70 kV, so that the thickness when dried was within 1 μm and the distance between adjacent electrodes was within 200 μm, and then the electrode pattern in the dried state was realized by drying at 100°C for 10 minutes.
[0075] In addition, the ceramic green sheet on which the electrode pattern was formed was sintered at 1000° C. for 2 hours in an air atmosphere to realize a sintered electrode pattern.
[0076] Thereafter, the following physical properties were measured for the electrode patterns in a dried state or the electrode patterns in a sintered state, and the results are shown in Table 1 or Table 2 below. 1. Average thickness and thickness uniformity The average thickness was measured using a stylus-type surface step measuring instrument, Alpha-Step (Dektak 150, Bruker).
[0077] In addition, the measured electrode surface was divided into five non-overlapping regions of the same area, and the average thickness of each of the five regions was measured. The average thickness value and the standard deviation for the five electrode regions were then calculated to calculate the thickness uniformity according to the following Equation 1. [Formula 1] Thickness uniformity (%) = [(Standard deviation (nm) for the average thickness of five regions) / (Average value (nm) for the average thickness of five regions)] x 100 2. Formation of a continuous electrode surface The dry electrode pattern was observed under an optical microscope to count the number of areas where the electrode material was not formed, measure the area, and evaluate the area on a scale of 0 to 5 according to the following criteria.
[0078] - If there is no part without electrodes, 5 points - The number of areas where electrodes are not formed is 1 to 2 and the area of the areas where electrodes are not formed is within 2% of the total area of the electrodes observed: 4 points - The number of areas without electrodes is between 2 and 5 and the area without electrodes is less than 5% of the total area of the electrodes observed: 3 points - The number of areas without electrodes is between 5 and 10 and the area without electrodes is between 5% and 10% of the total area of the electrodes observed: 2 points - The number of areas without electrodes is between 10 and 20 and the area without electrodes is between 5% and 15% of the total area of the electrodes observed: 1 point If the number of areas without electrodes exceeds 20 or the area without electrodes exceeds 15% of the total area of the electrodes observed, 0 points Relative shrinkage characteristics and thickness uniformity of sintered electrodes The shrinkage of the prepared sintered electrode pattern was measured, and the shrinkage of Example 4 was set to 100, and the degree of shrinkage of the other Examples was expressed as a relative percentage.
[0079] At this time, the shrinkage rate was calculated by measuring the average thickness of the dried electrode and the average thickness of the sintered electrode and calculating the value according to the following Equation 2. [Formula 2] Shrinkage rate (%) = (average electrode thickness after sintering (nm) / average electrode thickness after drying (nm)) × 100 In addition, the thickness uniformity was calculated by dividing the electrode surface whose thickness was measured into five random non-overlapping regions, measuring the average thickness for each of the five regions, and then calculating the average thickness value for the five electrode regions and the standard deviation therefor according to Equation 1 described above.
[0080] In Tables 1 and 2 below, "Ratio A" and "Ratio B" respectively refer to the ratio of particles having a particle size of at least twice the average particle size of the conductive metal powder and the ratio of particles having a particle size of 0.5 times or less of the average particle size among the total number of conductive metal powders. Also, "Ratio C" refers to the value obtained by dividing the average particle size of the ceramic powder by the average particle size of the conductive metal powder. Also, the content of the conductive metal powder is the content ratio based on the total weight of the electrode composition for electric spray, and the content of the ceramic powder is the content based on 100 parts by weight of the conductive metal powder.
[0081] [Table 1]
[0082] [Table 2]
[0083] As can be seen from Tables 1 and 2, In the case of the electrode composition according to Comparative Example 1, which contains a conductive metal powder with an average particle size exceeding 150 nm, the average thickness of the dry electrode is within 1.0 μm, but the thickness uniformity is very poor at 28.40%, so that the maximum thickness of the dry electrode exceeds 1.0 μm.
[0084] In addition, in the case of Examples 1 and 2, which contained conductive metal powder with an average particle size of 150 nm or less, the maximum thickness of the dried electrode formed after electrical spraying was 1.0 μm or less. However, in the case of Example 2, particles having a particle size more than twice the average particle size accounted for 26% of the conductive metal powder, resulting in a large number of coarse particles. As a result, the conductive metal powder settled at a high rate. As a result, the conductive metal powder was sprayed unevenly into the solution sprayed during electrical spraying, and the formability of a continuous electrode surface was significantly reduced compared to Example 1.
[0085] Meanwhile, in the case of Examples 3 and 4 in which the average particle size of the conductive metal powder is set to 100 nm or less, the average thickness of the dry electrode formed during electrical spraying under the same conditions is thinner than that of Example 1, and the thickness uniformity of the dry electrode and the formability of a continuous electrode surface are increased.
[0086] However, compared to the electrode composition of Example 3, the electrode composition of Example 4 has a further reduced ratio of particles having a particle size two or more times larger than the average particle size of the conductive metal powder, which increases the content uniformity of the conductive metal powder sprayed during electrical spraying. Also, the average particle size of the ceramic powder is further adjusted relative to the average particle size of the conductive metal powder, so that the thickness uniformity of the dry electrode, the formability of a continuous electrode surface, and the shrinkage characteristics and thickness uniformity of the sintered electrode are very excellent.
[0087] Also, in Example 6, in which a ceramic powder having an average particle size less than 0.1 times that of the conductive metal powder was mixed, the thickness uniformity of the dry electrode was lower than in Example 4, and the shrinkage characteristics and thickness uniformity of the sintered electrode were lowered. Also, in Example 7, in which a ceramic powder having an average particle size more than 0.5 times that of the conductive metal powder was mixed, the shrinkage characteristics of the sintered electrode were significantly lowered.
[0088] In addition, when the content of conductive metal powder exceeded 30 wt%, the increased electrical conductivity of the electrospray composition affected the electrospray, resulting in a decrease in the formability of a continuous electrode surface compared to Example 4, and a decrease in the thickness uniformity of the dry electrode.
[0089] Also, in the case of Example 10 in which the content of conductive metal powder was less than 10 wt %, the formability of a continuous electrode surface and the uniformity of the dry thickness were deteriorated compared to Example 9.
[0090] Meanwhile, in Example 12, in which the ceramic powder content exceeded the preferred range, the shrinkage of the sintered electrode was significantly increased compared to Example 4, and in Example 14, in which the ceramic powder content was below the preferred range, the effect of reducing electrical conductivity was minimal, and therefore the thickness uniformity of the resulting dry electrode was reduced. <Example 15> The same procedure as in Example 1 was carried out to prepare the electrode composition for photosensitive electrospray, but the conductive metal powder, which is nickel and whose particle size was adjusted in Example 1, and the ceramic powder were added to a mixed solvent in which dihydroterpineol and dihydroterpineol acetate were mixed in a weight ratio of 1:1 as the solvent, and the binder resin, which includes 75% by weight of an acrylate copolymer in which 19.5 mol % of methacrylic acid, 38.5 mol % of methyl methacrylate, and 42 mol % of isobornyl methacrylate were copolymerized and 25% by weight of a polyvinyl butyral resin, and the photosensitive resin was mixed with the conductive metal powder, which is nickel and whose particle size was adjusted in Example 1 ... ceramic powder and the photosensitive resin had a weight average molecular weight of about 10,000 and contained 75% by weight of an acrylate copolymer in which 19.5 mol % of methacrylic acid, 38.5 mol % of methyl methacrylate, and 42 mol % of isobornyl methacrylate were copolymerized, and 25% by weight of a polyvinyl butyral resin. To 100 parts by weight of resin, 13 parts by weight of pentaerythritol triacrylate as a multifunctional monomer and azobisisobutyronitrile as a photoinitiator were mixed. Specifically, to 100 parts by weight of conductive metal powder, 6.8 parts by weight of ceramic powder, 8 parts by weight of the total weight of binder resin and multifunctional monomer, and 1 part by weight of photoinitiator to 100 parts by weight of photosensitive resin were mixed, and the weight of conductive metal powder was 25% by weight of the total composition, to prepare an electrode composition for electrospray as shown in Table 3 below, which has a viscosity of 80 cps at 25°C.
[0091] The viscosity of the prepared electrospray electrode composition was measured using a Brookfield rotational viscometer LV according to ISO 554 under conditions of a temperature of 25, a relative humidity of 65%, and a rotation speed of 10 rpm. <Examples 16 to 28> Electrode compositions for electrical spray were prepared by carrying out the same procedure as in Example 15, but the content, average particle size, particle size distribution of the conductive metal powder, the content, average particle size of the ceramic powder, and / or the viscosity of the electrode composition were changed as shown in Table 3 or Table 4 below.
[0092] The ceramic powder used here had its particle size adjusted through wet classification so that particles with a particle size of more than twice the average particle size were within 10% of the total ceramic powder, and particles with a particle size of less than 0.5 times the average particle size were within 10% of the total ceramic powder. <Comparative Example 2> The electrode composition for electric spray was prepared in the same manner as in Example 15, but the average particle size of the conductive metal powder was changed as shown in Table 3 below. <Experimental Example 2> On the ceramic green sheet used in Experimental Example 1, the photosensitive electrode compositions for electrospray according to Examples 15 to 28 and Comparative Example 2 were electrosprayed using an electrospray device at a discharge speed (3 ml / min per hole) under conditions of 18°C, relative humidity 30%, an air gap (distance between the nozzle and the ceramic green sheet surface) of 24 cm, and an applied voltage of 70 kV to a thickness of 1 μm or less when dried, and then dried at 65°C for 10 minutes to obtain a photosensitive electrode layer in a dried state.
[0093] Then, a mask was placed on the photosensitive electrode layer to have a predetermined electrode line pattern, and the layer was exposed to UV light at an intensity of 550 mJ and developed for 30 seconds using a developer solution of 3 wt% Na2CO3 solution to realize an electrode pattern. Then, the ceramic green sheet on which the electrode pattern was formed was sintered at 1000°C for 2 hours in an air atmosphere to realize a sintered electrode pattern.
[0094] Thereafter, the following physical properties were measured for the dried photosensitive electrode layer, the electrode pattern developed after exposure, or the sintered electrode pattern, and the results are shown in Table 3 or Table 4 below.
[0095] At this time, (1) average thickness and thickness uniformity, (2) formability of a continuous electrode surface for the dried photosensitive electrode layer, and (3) relative shrinkage characteristics and thickness uniformity of the sintered electrode were evaluated in the same manner as in Experimental Example 1. Undercut ratio After exposure and development, the electrode pattern was cut at 10 random points, SEM images were taken, and the top and bottom widths of the electrode cross section at each point were measured. The undercut ratio at each point was calculated as the percentage of the bottom width to the top width (bottom width (μm) x 100 / top width (μm)), and the average value of the undercut ratios for the 10 points was calculated. The closer the undercut ratio is to 100%, the better the exposure to the bottom side of the electrode, and the better the quality of the electrode.
[0096] In addition, in Tables 3 and 4 below, "Ratio A" and "Ratio B" respectively refer to the ratio of particles having a particle size of at least twice the average particle size of the conductive metal powder and the ratio of particles having a particle size of 0.5 times or less of the average particle size among the total number of conductive metal powders. Also, "Ratio C" refers to the value obtained by dividing the average particle size of the ceramic powder by the average particle size of the conductive metal powder. Also, the content of the conductive metal powder is the content ratio based on the total weight of the electrode composition for photosensitive electrospray, and the content of the ceramic powder is the content based on 100 parts by weight of the conductive metal powder.
[0097] [Table 3]
[0098] [Table 4]
[0099] As can be seen from Tables 3 and 4, In the case of the electrode composition of Comparative Example 2 containing a conductive metal powder with an average particle size exceeding 150 nm, the average thickness of the dry electrode was within 1.0 μm, but the thickness uniformity was very poor at 28.40%, and the maximum thickness of the dry electrode exceeded 1.0 μm.
[0100] In addition, in the cases of Examples 15 and 16, which contained conductive metal powder with an average particle size of 150 nm or less, the maximum thickness of the dried electrode formed after electrospraying was 1.0 μm or less, but in the case of Example 16, particles having a particle size of more than twice the average particle size reached 26% of the conductive metal powder, and there were many coarse particles, which resulted in a high settling speed of the conductive metal powder, and therefore the conductive metal powder was sprayed non-uniformly into the solution sprayed during electrospraying, and the formability of a continuous electrode surface was significantly reduced compared to Example 15. In addition, it was found that the quality of the realized electrode was reduced due to the deepening of undercuts caused by improper exposure to light on the lower side of the electrode.
[0101] Meanwhile, in the case of Examples 17 and 18 in which the average particle size of the conductive metal powder is set to 100 nm or less, the average thickness of the dry electrode formed during electrical spraying under the same conditions is thinner than that of Example 1, and the thickness uniformity of the dry electrode and the formability of a continuous electrode surface are increased.
[0102] However, compared to the electrode composition of Example 17, the electrode composition of Example 18 has a further reduced ratio of particles having a particle size two or more times larger than the average particle size of the conductive metal powder, thereby increasing the content uniformity of the conductive metal powder sprayed during electrospraying, and is mixed so that the average particle size of the ceramic powder is further controlled compared to the average particle size of the conductive metal powder, thereby realizing excellent thickness uniformity of the dry electrode, continuous electrode surface formability, and shrinkage characteristics and thickness uniformity of the sintered electrode.
[0103] Also, in Example 20, in which a ceramic powder having an average particle size less than 0.1 times that of the conductive metal powder was mixed, the thickness uniformity of the dry electrode was lower than in Example 18, and the shrinkage characteristics and thickness uniformity of the sintered electrode were lowered. Also, in the case of Example 21, in which a ceramic powder having an average particle size more than 0.5 times that of the conductive metal powder was mixed, the shrinkage characteristics of the sintered electrode were significantly lowered.
[0104] In addition, when the content of conductive metal powder exceeded 30 wt%, the increased electrical conductivity of the electrospray composition affected electrospray, resulting in a decrease in the formability of a continuous electrode surface and a decrease in the thickness uniformity of the dry electrode compared to Example 18. In addition, it was found that the undercut deepened because the exposure of the lower side of the electrode was not performed properly.
[0105] Also, in the case of Example 24 in which the content of conductive metal powder was less than 10 wt %, the formability of a continuous electrode surface and the uniformity of the dry thickness were deteriorated compared to Example 23.
[0106] Meanwhile, in Example 26, in which the ceramic powder content exceeded the preferred range, the shrinkage of the sintered electrode was significantly increased compared to Example 18, while in Example 28, in which the ceramic powder content was below the preferred range, the effect of reducing electrical conductivity was minimal, and therefore the thickness uniformity of the resulting dry electrode was reduced compared to Example 27.
[0107] Although one embodiment of the present invention has been described above, the concept of the present invention is not limited to the embodiment presented in this specification, and a person skilled in the art who understands the concept of the present invention may easily propose other embodiments by adding, changing, deleting, or adding components within the scope of the same concept, which may also be considered to fall within the scope of the concept of the present invention.
Claims
1. An electrode composition for electrospray for implementing an electrode having an average thickness of 1.0 μm or less when dried, comprising a conductive metal powder having an average particle size of 150 nm or less, a ceramic powder, a binder resin, and a solvent; The ceramic powder is contained in an amount of 4 to 10 parts by weight based on 100 parts by weight of the conductive metal powder. Electrode compositions for electrospray.
2. The electrode composition for electrical spray according to claim 1, which is an electrode composition for realizing an internal electrode of a multilayer ceramic part.
3. 10. The electrical spray electrode composition of claim 1, wherein the conductive metal powder has an average particle size of 80 nm or less.
4. 2. The electrode composition for electrical spray according to claim 1, wherein the number of particles having a particle size of at least twice the average particle size is 20% or less of the total number of the conductive metal powder, and the number of particles having a particle size of 0.5 times the average particle size or less is 20% or less of the total number of the conductive metal powder.
5. 2. The electrode composition for electrical spray according to claim 1, wherein the conductive metal powder comprises at least one of a metal selected from the group consisting of Ni, Mn, Cr, Al, Ag, Cu, Pd, W, Mo, and Co, an alloy containing at least one of these metals, and a mixed metal containing at least two of these metals.
6. 2. The electrical spray electrode composition of claim 1, wherein the ceramic powder has an average particle size that is 0.1 to 0.5 times the average particle size of the conductive metal powder.
7. 2. The electrical spray electrode composition of claim 1, wherein the ceramic powder comprises at least one ceramic powder selected from the group consisting of titania, alumina, silica, cordierite, mullite, spinel, barium titanate, calcium zirconia, and zirconia.
8. 2. The electrode composition for electrical spray according to claim 1, wherein the conductive metal powder is present in an amount of 10 to 30% by weight based on the total weight of the composition.
9. 2. The electrode composition for electrical spray according to claim 1, wherein the binder resin is included in an amount of 2 to 13 parts by weight based on 100 parts by weight of the conductive metal powder.
10. 2. The electrode composition for electrical spray according to claim 1, wherein the binder resin comprises 30 to 60 parts by weight of ethyl cellulose per 100 parts by weight of polyvinyl butyral.
11. The electrode composition for electrical spraying of claim 1, comprising a photosensitive resin as the binder resin, and further comprising a monomer and a photoinitiator.
12. The electrode composition for electrical spray according to claim 11, wherein the total weight of the binder resin and the monomer is 2 to 13 parts by weight per 100 parts by weight of the conductive metal powder.
13. 10. The electrical spray electrode composition of claim 1, wherein the ceramic powder has an average particle size of 45 nm or less.
14. The electrical spray electrode composition of claim 1, having a viscosity of 50 to 150 cps at 25°C.
15. An electrode having an average thickness of 1.0 μm or less, the electrode being formed by electrospraying the electrospray electrode composition according to any one of claims 1 to 14 onto a predetermined area and then drying.
16. 16. The electrospray electrode of claim 15, having a thickness uniformity of 10% or less.
17. 20. A multilayer ceramic component comprising an internal electrode to which the electrospray electrode of claim 15 has been sintered.
Citation Information
Patent Citations
Process for producing ceramic green sheet
JP2006210820A
Composite film and manufacturing method and manufacturing apparatus of composite film pattern
JP2020152813A
Paste for internal electrode, and manufacturing method of laminate ceramic electronic component
JP2020188111A
Conductive paste and capacitor element for constituting solid electrolytic capacitor using same
WO2015037368A1